1998
DOI: 10.1046/j.1524-475x.1998.60606.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous lateral electric fields around bovine corneal lesions are necessary for and can enhance normal rates of wound healing

Abstract: The strength of the electric fields in the vicinity of 1.5 mm circular lesions in the bovine cornea has been found to influence the rate of re-epithelization. A decrease in the field strength by submersion of the lesions or by treating the lesions with the Na+-channel blocker, benzamil, significantly retarded healing. An increase in the field strength of lesions treated with Na+-depleted Hanks' solution, by the addition of direct current, increased epithelization. Epithelization was fastest in wounds with fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 10 publications
3
67
0
Order By: Relevance
“…The lateral EF is driven by the transepithelial potential through the low-resistance wound pathway, creating a negative pole (cathode) at the center of the wound (Ojingwa and Isseroff, 2003). Endogenous direct current (DC) EFs of 40-200 mV mm -1 have been measured near wounds in mammalian epithelia (Barker et al, 1982;Chiang et al, 1992;McGinnis and Vanable, 1986;Sta Iglesia et al, 1996;Sta Iglesia and Vanable, 1998). Human neonatal keratinocytes do indeed sense the EF within minutes, re-form their lamellipodia facing the cathode and migrate directionally in physiological DC EFs of 100 mV mm -1 in vitro, a process known as galvanotaxis (Nishimura et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The lateral EF is driven by the transepithelial potential through the low-resistance wound pathway, creating a negative pole (cathode) at the center of the wound (Ojingwa and Isseroff, 2003). Endogenous direct current (DC) EFs of 40-200 mV mm -1 have been measured near wounds in mammalian epithelia (Barker et al, 1982;Chiang et al, 1992;McGinnis and Vanable, 1986;Sta Iglesia et al, 1996;Sta Iglesia and Vanable, 1998). Human neonatal keratinocytes do indeed sense the EF within minutes, re-form their lamellipodia facing the cathode and migrate directionally in physiological DC EFs of 100 mV mm -1 in vitro, a process known as galvanotaxis (Nishimura et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…We used the EFs within this range because the strength of endogenous dcEFs in animal body is known to be 50-500 mV/mm. 10,11,30 The activity of the cells in the device was not affected under a 540 mV/mm dcEF within 8 h. However, an EF strength larger than 900 mV/mm caused cell death in a few hours. Without the dcEF treatment, the migration of CL1-5 cells was random.…”
Section: Resultsmentioning
confidence: 99%
“…"All the electric phenomena which it manifests being due to internal molecular changes associated with activity or injury" (in his work Researches on Animal Electricity, from 1848 to 1884). Micro-electric current had been detected in wounds in both epithelial and non-epithelial tissues in human and other mammals using various modern techniques [84][85][86][87][88][89][90][91][92]. Sta et al [84] and Nuccitelli et al [85] reported the endogenous lateral electric fields around corneal and other epithelial lesions.…”
Section: The Identity Of Electric Field Lateralization Induced By Dismentioning
confidence: 99%
“…Micro-electric current had been detected in wounds in both epithelial and non-epithelial tissues in human and other mammals using various modern techniques [84][85][86][87][88][89][90][91][92]. Sta et al [84] and Nuccitelli et al [85] reported the endogenous lateral electric fields around corneal and other epithelial lesions. Song et al [86] detailed the features: "In cornea and skin, a laterally oriented, wound-induced d.c. (direct current) electric field is generated instantaneously when the epithelium is damaged, and it persists until re-epithelialization restores the electrical resistance barrier function of the epithelium".…”
Section: The Identity Of Electric Field Lateralization Induced By Dismentioning
confidence: 99%
See 1 more Smart Citation